2021
DOI: 10.1016/j.jare.2020.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng: A bibliometric analysis of 40-year journey of global clinical trials

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…In recent years, domestic and foreign scholars have conducted pharmacological studies, clinical observations, and epidemiological investigations on the effective ingredients of ginseng, and the results have confirmed that ginseng has improved microcirculation, improved tissue antihypoxia ability, and inhibited platelet aggregation, antitumor, and antiaging, antiradiation, antifatigue, and other biological activities. [ 27 , 28 ] In fatigue, previous studies have found that ginseng can improve thinking and physical activity. [ 29 , 30 ] However, large samples of clinical research data are insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, domestic and foreign scholars have conducted pharmacological studies, clinical observations, and epidemiological investigations on the effective ingredients of ginseng, and the results have confirmed that ginseng has improved microcirculation, improved tissue antihypoxia ability, and inhibited platelet aggregation, antitumor, and antiaging, antiradiation, antifatigue, and other biological activities. [ 27 , 28 ] In fatigue, previous studies have found that ginseng can improve thinking and physical activity. [ 29 , 30 ] However, large samples of clinical research data are insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, a systematic review aiming to include all clinical trials involving all forms of ginseng was published [141]. Of the 121 retained studies that evaluated safety, 41.6% reported no adverse events, 31.6% reported no significant difference between groups in adverse events, and 26.6% reported no serious adverse events [141]. Mild adverse events included dizziness, headaches, diarrhea, insomnia, hypoglycemia, and nausea [141].…”
Section: Safetymentioning
confidence: 99%
“…Of the 121 retained studies that evaluated safety, 41.6% reported no adverse events, 31.6% reported no significant difference between groups in adverse events, and 26.6% reported no serious adverse events [141]. Mild adverse events included dizziness, headaches, diarrhea, insomnia, hypoglycemia, and nausea [141]. Due to the scarcity of human research involving the ginseng berry and its extracts, establishing clinical safety remains essential.…”
Section: Safetymentioning
confidence: 99%
“…Recently, the focus on naturally-occurring bioactive for therapeutic purposes has grown, and specifically with concerns to neuropsychiatric treatment, an increasing amount of natural products formulations has become widespread with the main goal of avoiding or even decreasing the use of psychotropic drugs (W. Chen et al, 2021;Al Mamun et al, 2021;Shandilya et al, 2022). Many medicinal plants, their derived extracts and even isolated constituents have been addressed for their therapeutic abilities in ADHD, in vitro and in vivo experiments, and even clinical studies, with Acorus gramineus Aiton, Paecilomyces tenuipes, Rhodiola rosea L., Psoralea corylifolia L., Hypericum perforatum L., Valeriana officinalis L., Ginkgo biloba L. In an in vitro experiment, the bioactive compound α-asarone isolated from A. gramineus Aiton led to a reduction in the elevated acetylcholinesterase activity at the same time that increased the m1 muscarinic acetylcholine receptor expression (Qiu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%